When Bad News Becomes Routine: Slowly-Developing Problems Moderate Government Responsiveness. (March 2023) - Epp, Derek A.; Thomas, Herschel F.
Established theories of the policy process recognize the challenges governments face in processing information. We examine how the ways in which public problems develop over time condition subsequent policy actions. We contend that policymakers will become routinized to and consequently under-respond to the accumulating signals of slowly-developing problems (i.e., those featuring long runs of relatively small changes). Event history analyses leverage variation across the United States in the development of the COVID-19 pandemic and the subsequent implementation of social distancing policies. Looking across the 50 states and Washington DC, we find that regions that saw protracted deterioration in their health situation were slower to respond with social distancing than those that saw an abrupt deterioration to the same point. These results highlight the risks associated with problems that worsen only gradually over time.